THE EFFECTIVENESS OF PROJECT-BASED LEARNING IN ENHANCING STUDENTS' SPEAKING SKILLS IN ENGLISH - Kurniawan, Yulius (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effectiveness of using the Project-Based Learning (PBL) method in enhancing students' speaking skills in English as a Foreign Language (EFL) learning. PBL is an instructional approach that engages students in real-world tasks requiring them to actively use English in authentic situations. In this research, a literature review was conducted by analyzing various previous studies exploring the impact of PBL on speaking skills, focusing on aspects such as student engagement, creativity, and language use in real-life communication contexts. The findings indicate that PBL can significantly enhance students' motivation, confidence, and speaking abilities. Various types of projects, such as vlogs and digital storytelling, have proven effective in providing students with opportunities to practice speaking in a more free and creative manner. Moreover, peer interaction in collaborative-based projects further strengthens students' speaking competence. However, challenges in implementing PBL, such as the need for proper guidance and alignment with students' proficiency levels, should be considered. Overall, PBL offers great potential in developing speaking skills in English more effectively and comprehensively.